Strategi Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu dalam Meningkatkan Investasi di Kota Pekanbaru - Regiyati, Salsabilla; Rusli, Zaili (Penerbit Goodwood, 2021)
Purpose: The purpose of this research is to determine the strategies and obstacle of The Service of Investment and The One Stop Service (DPMPTSP) in increasing the investment in Pekanbaru City. Research methodology: This research used a qualitative method with a descriptive approach. Results: The result of this research is that the strategy of DPMPTSP Pekanbaru city has not been carried out optimally because of the obstacles to the Covid-19 pandemic so that activities have stopped temporarily, but investment continues to increase. Limitations: In this study, the researcher has a lack of informants. The informants are the investors who invest in the Pekanbaru City. Contribution: Theoretically, this research serves as a continuous comparison medium for future research by having the same topic or problem. It can bring up problem-solving models or new ideas in developing government strategies, especially in this research related to investment. Practically, it can evaluate the DPMPTSP of Pekanbaru City and other regional apparatus organizations in terms of implementation and formulation of strategies to achieve goals, especially in the investment sector.